Optimizing patient outcome in intracranial tumor surgery: a detailed prospective study of adverse events and mortality reduction strategies in neurosurgery - Lenga, Pavlina; Kleineidam, Helena; Unterberg, Andreas; Dao Trong, Huy Philip (Acta neurochirurgica, 2024)
Introduction: Brain tumor surgery represents a critical and high-risk area within the field of neurosurgery. Our study aims to offer a comprehensive analysis of adverse events (AEs) from a prospectively maintained database at a leading neurosurgical tertiary center, with a specific focus on different types of tumor entities. Methods: From January 2022 to September 2023, our study focused on adult patients, who underwent surgery for intracranial tumors. Each patient in this demographic was thoroughly assessed for adverse events (AEs) by their attending physicians at discharge. An AE was defined as any event occurring within the first 30 days post-surgery. Results: A total of 1173 patients with an average age of 57.4 ± 15.3 years underwent surgical procedures. The majority of these surgeries were elective, accounting for 93.4% (1095 out of 1173), while emergency surgeries constituted 13.9% (163 out of 1173). The incidence of surgery-related AEs was relatively low at 12.7%. The most common surgical indications were meningioma and glioma pathologies, representing 31.1% and 28.2% of cases, respectively. Dural leaks occurred in 1.5% of the cases. Postoperative hemorrhage was a significant complication, especially among glioma patients, with ten experiencing postoperative hemorrhage and eight requiring revision surgery. The overall mortality rate stood at 0.8%, corresponding to five patient deaths. Causes of death included massive postoperative bleeding in one patient, pulmonary embolism in two patients, and tumor progression in two others. Conclusions: Surgical interventions for intracranial neoplasms are inherently associated with a significant risk of adverse events. However, our study’s findings reveal a notably low mortality rate within our patient cohort. This suggests that thorough documentation of AEs, coupled with proactive intervention strategies in neurosurgical practices, can substantially enhance patient outcomes.
Gesehen am 12.07.2024